A case of rheumatic fever with acute post-streptococcal glomerulonephritis and nephrotic syndrome caused by a cutaneous infection with beta-hemolytic streptococci - Carsten Sauer Mikkelsen; Allan Gelvan; Ahmad Ibrahim; Karin Ladefoged (PAGEPress Publications, 2010)
A middle-aged patient of Greenlandic origin was referred for skin infection of the leg. An initial minor trauma of the skin of the distal right lower extremity was complicated by bullous erysipelas which cultured positive for group A β-hemolytic streptococci (GABHS). The clinical condition deteriorated and necrotizing fasciitis developed despite relevant surgical and antibiotic treatment. Approximately 3 weeks later, the patient developed arthralgia, impaired renal function with azotemia, hypertension and severe nephrotic syndrome with periorbital and peripheral edema. A kidney biopsy demonstrated endocapillary glomerulonephritis. Concomitantly, carditis with chest pain, moderately reduced left ventricular ejection fraction and mitral regurgitation were noted. The patient had no signs of pharyngitis in the whole period. The patient thus contracted poststreptococ glomerulonephritis and furthermore she fulfilled the criteria of acute rheumatic fever following a GABHS skin infection. We suggest a possible relation between a virulent GABHS clone causing NF and ARF.